Pengaruh Eksposur Meme Politik Terhadap Minat Politik Generasi Z di Yogyakarta - Ambrosius Samuel Aprianto; Risvi Khairil Anam Ahmad; Jesyca Adelya Putri (CV. ITTC INDONESIA, 2026)
The development of digital technology and social media has given rise to a growing variety of informal forms of political content, one of which is political memes that are widely consumed by Generation Z. generation Z, who tend to have a relaxed and humorous nature, often believe that meme-based content can attract the attention of young people to political issues due to its lighthearted packaging. The objective of this study is to examine the extent or significance of the influence of political exposure on the political interest of generation Z in Yogyakarta. This research uses a descriptive quantitative approach and a questionnaire distribution method targeting social media-active generation Z as a means of data collection. The results indicate that exposure to political memes does not have a significant impact in increasing the political interest of generation Z, particularly in Yogyakarta